2022
DOI: 10.4314/dujopas.v7i4b.4
|View full text |Cite
|
Sign up to set email alerts
|

The performance measure analysis on the states classification in Markov Chain

Abstract: The system being modelled is assumed to occupy one and only one state at any moment in time and its evolution is represented by transitions from state to state. Also, the physical or mathematical behaviour of this system may be represented by describing all the different states it may occupy and by indicating how it moves among these states. In this work, the concept of the classification of groups of states, between states that are recurrent, meaning that the Markov chain is guaranteed to return to these stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…Agboola and Ayoade (2021) investigated a block structure that arises frequently when modeling queueing systems to provide some insight into the solutions of stationary distribution of Markov chain. Agboola and Ayinde (2021) analysed the concept of the classification of groups of states, between states that are recurrent, transient to provide some insight into the performance measure analysis such as the mean first passage time, the mean recurrence time of state as well as recurrence iterative matrix. Agboola (2021) computed the solutions and algorithms for lower -upper triangular matrix approach and the Grassmann -Taksar -Heyman to obtained the stationary distribution vectors in Markov chain.…”
Section: Introductionmentioning
confidence: 99%
“…Agboola and Ayoade (2021) investigated a block structure that arises frequently when modeling queueing systems to provide some insight into the solutions of stationary distribution of Markov chain. Agboola and Ayinde (2021) analysed the concept of the classification of groups of states, between states that are recurrent, transient to provide some insight into the performance measure analysis such as the mean first passage time, the mean recurrence time of state as well as recurrence iterative matrix. Agboola (2021) computed the solutions and algorithms for lower -upper triangular matrix approach and the Grassmann -Taksar -Heyman to obtained the stationary distribution vectors in Markov chain.…”
Section: Introductionmentioning
confidence: 99%
“…The Jacobi iterative method is a fundamental technique that is widely applied in various fields (Chalermwut et al, 2023). Islam (2023) applied Jacobi to solve linear systems using theory, data, and high-performance computing, while Agboola et al (2023) solved the stationary distribution of a markov chain using the Jacobi method. Meanwhile, Zhen et al (2023) found a new way of solving fuzzy linear systems using the Jacobi method, and Huang and Jia (2023) did an approximate orthogonal tensor diagonalization of Jacobi convergence.…”
Section: Introductionmentioning
confidence: 99%